Theatrical Complicity as a Medium of Emancipation - Nielsen, Thomas Rosendal (Nordic Theatre Studies, 2015)
How do we find a solution when we ourselves are the problem? This is the question posed by two contemporary performances that frame the spectator as an accomplice in the exploitation and representation of suffering and violence in a globalized and mediatized world: Sálo (2010), based on Pier Paolo Passolini’s film by the same name (1975), by the Danish performance group SIGNA in cooperation with Teater Republique; and the Royal Court Theatre’s production of Tim Crouch’s The Author (2009), co-directed by Karl James and a smith. By applying the systems theory of Niklas Luhmann, the two performances are analysed and compared as elaborately structured games of observation, where the spectators are made to observe their own acts of spectating as complicity in the reproduction of violence caused by theatrical representation. Jaques Rancière’s paradox of the spectator and Josette Féral’s concept of theatricality are re-described in a systems theoretical perspective in order to show how the theatrical attribution of guilt to the spectator can work as a medium of emancipation. The explication of the different dramaturgies makes it possible to distinguish between how self-righteous, self-examining, progressive and ‘tragicist’ conceptions of emancipation are given form in different ways and measures in the two performances. In this way, the article aims to contribute to the qualification and expansion of a critical discourse on participatory theatre and performance beneath the loosely defined horizon of a modern theatre of emancipation.